Impact of prostate volume on oncologic, perioperative, and functional outcomes after radical prostatectomy. Issue 13 (12th June 2015) - Mandel, Philipp; Weinhold, Philipp; Michl, Uwe; Huland, Hartwig; Graefen, Markus; Tilki, Derya
ABSTRACT Background The impact of prostate volume (PV) on oncologic, perioperative and functional outcomes after radical prostatectomy (RP) remains controversial, as recent studies present inconsistent results. We studied the influence of PV on outcomes in a large single center dataset and summarized the existing literature. Methods 5, 477 patients who underwent RP between January 2008 and December 2011 were analyzed. The impact of PV on biochemical recurrence (BCR) and metastasis‐free survival (MFS) was assessed using Kaplan–Meier curves and multivariate Cox proportional hazard model. Uni‐ and multivariate logistic regressions were used to estimate the impact of PV on surgical margin (SM), 1‐week, 3‐months and 12‐months continence and 3‐months and 12‐months potency. Finally, the impact of PV on intraoperative blood loss was analyzed using uni‐ and multivariate linear regressions. Results Median follow‐up was 36.1 months. Overall, 16.5% of patients recurred during the follow‐up period. The mean preoperative PV was 43.3 ml. One‐week, 3‐months and 12‐months continence rates were 55.6%, 69.3%, and 87.4% for patients with PV ≥ 70 compared to 64.4%, 78.3%, and 92.1% for patients with PV < 30, respectively. Three‐months and 12‐months potency rates were 37.1% and 54.8% for men with large glands (≥70) and 56.3% and 65.0% for men with PV < 30. In multivariate analysis, continence at 1 week, 3 months and 12 months was significantly worse in patients with glands ≥70 ml, while potency was not influenced by PV in multivariate analysis. There was a higher mean blood loss (P < 0.001) in patients with larger glands. In univariate analysis, higher PV was significantly associated with lower BCR (P = 0.019), but not with metastasis free survival (P = 0.112). Conclusions PV significantly influences BCR‐free survival only in univariate analysis. Especially early (1‐week and 3‐months) postoperative continence is negatively affected by higher PV in multivariate analysis, while PV did not influence potency after adjusting for further covariates in a specialized high‐volume institution. Prostate 75:1436–1446, 2015. © 2015 Wiley Periodicals, Inc.